Identification of quality indicators to monitoring of a renal transplant service - Treviso, Patrícia; Brandão, Flávio Henrique; Saitovitch, David (Brazilian Journal of Transplantation, 2010)
Purpose: To identify major quality indicators of a Renal Transplant Service, according to the professionals and patients’ opinion. Method: Exploratory and descriptive study, quantitative analysis, information gathered through an aimed questionnaire with open and close questions. Sample (n = 133) consisted by assistant and administrative professionals and by patients. Result: There was no relevant difference concerning the importance of the indicators presented, according to the professionals’ opinion. It was observed a statistic difference as to: the need of additional indicators, according to the assistant professionals (p=0,046) and the administrative professionals’ opinion (p=0,011). Patients emphasized the need of indicators related to the humanization of the care. Conclusion: The present institutional indicators in hospitals are insufficient and they do not comply with the present reality of a transplant program. This study allowed the identification of a consistent list of 23 specific indicators that can be used by Renal Transplant Services.